Documenting non‐accidental injury patterns in a dog abuse investigation: A collaborative approach between forensic anthropology and veterinary pathology. Issue 2 (23rd November 2021) - Bartelink, Eric J.; Clinkinbeard, Shannon; Spessard, Crystal; Kilmartin, Aoife; Spangler, William L.
Abstract: This case study demonstrates how animal abuse investigations can benefit from collaboration between forensic anthropologists and veterinary pathologists, especially in investigations involving trauma assessment of skeletal remains. In 2009, four deceased dogs were excavated from a residential property in conjunction with a case of suspected animal abuse. The decomposed remains were skeletonized to permit assessment of biological profiles, individualization, and trauma analysis. Each dog was identified based on their sex, age‐at‐death, fur coloration patterns, and through investigative information. The analysis conducted by forensic anthropologists in collaboration with a veterinary pathologist revealed evidence of perimortem blunt force trauma on all four skeletons. The distribution and severity of the injuries, including fractures concentrated mainly on the axial skeleton (i.e., skull, thorax, and vertebral column) and pelvis, are consistent with documented cases of non‐accidental injury (NAI) reported in the literature. Healed rib fractures were also noted on one of the dogs, and likely occurred a few weeks prior to death, further supporting a diagnosis of NAI. The skeletal trauma findings were inconsistent with the dog owner's account of how each dog had died and were instrumental in resolving the investigation.